Early Fault Detection via Multiple Feature Fusion and Ensemble Learning - Song, Wenbin; Wu, Di; Shen, Weiming; Boulet, Benoit (IEEE sensors journal, 2024)
Early fault detection (EFD) of rotating machines is important to decrease the maintenance cost and improve the mechanical system stability. One of the key points of EFD is developing a generic and robust model for different equipment. Most existing EFD methods focus on learning fault representation by one type of feature. However, a combination of multiple features can capture a more comprehensive representation. In this article, we propose an EFD method based on multiple feature fusion with stacking architecture (M2FSA). The proposed method can extract generic and discriminative features to detect early faults by combining time domain (TD), frequency domain (FD), and time-frequency domain (TFD) features. To unify the dimensions of the different domain features, stacked denoising autoencoder (SDAE) is used to learn deep features in three domains. The proposed method is tested on three bearing datasets and a motor dataset. The results demonstrate that the proposed method is better than existing methods in both sensibility and reliability.